LAND USE AND LAND COVER MAPPING IN DETAILED SCALE: A CASE STUDY IN SANTA ROSA DE LIMA-SC - Macedo, Rodrigo de Campos; Schmitt Filho, Abdon Luiz; Farley, Joshua C.; Fantini, Alfredo Celso; Cazella, Ademir Antonio; Sinisgalli, Paulo Antonio de Almeida (Boletim de Ciências Geodésicas, 2018)
It is challenging to reconcile large scale data with the dynamic characteristics present in land use.Such dynamism requires data with a high repetition of sampling. An alternative is the integration of data of high spatial resolution and low temporal resolution, with that of high temporal resolution and low spatial resolution. The aim addressed in this article is related to the integration of aerial photographs and temporal series for land use and land cover mapping in high detail scale. We conducted a case study in Santa Rosa de Lima-SC. The main data used was the aerial survey that overlaid the state of Santa Catarina, executed in 2010/2011. The interpretation key included typical elements of hotointerpretation (color, texture, size, shape), aiming to classify the land use and land cover classes. The mapping evaluation resulted in 75.6% global accuracy, ranging from 54% Grassland and Wetlands) to 96% (Water Bodies and Rocks). Such results are considered satisfactory. The integration of high-resolution images with high temporal resolution data has enabled the iscrimination between classes that present great difficulties of separability. Such discrimination is essential in the territorial management processes of Encosta da Serra and the municipality of Santa Rosa de Lima.